Wrong place, wrong time [compact disc, unabridged] - Kane, Andrea (Romantic sounds audio., 2006)
When Sally Montgomery accompanies her handsome boss Frederick Pierson on a quiet country weekend, she enjoys the first evening. But when she discovers his battered body the next morning, she runs for her life. Now it's up to Pete, her ex-husband and former New York policeman, to keep her safe and find the killer.